Hubungan Cara Penanganan Pestisida dengan Tingkat Keracunan Pestisida Pada Petani di Dusun Banjarrejo Desa Kembang Kuning Kecamatan Cepogo Kabupaten Boyolali - Sukarno Putri, Marisa, Heru Subaris K, SKM., M.Kes, Dwi Astuti, SKM., M.Kes (2016)
Exposure to pesticides was cause of pesticide poisoning in farmers by looking at blood levels of cholinesterase farmers. This study aims to determine the relationship of pesticide handled to the level of pesticide poisoning to farmers in Banjarrejo Kembang Kuning Cepogo. Handled of pesticides consist of how pesticide storages, way mixed pesticides, and by washed spray equipment. This study was an observational study with cross sectional design. The population in this study were 40 respondents with male gender and sample collection techniques that exhaustive sampling. Fisher Exact was to used as a bivariate analysis with significance 0,05. The results of the bivariate analysis shows that there was a relationship between how the storage of pesticides with levels of pesticide poisoning (0,016), way of mixed pesticides with levels of pesticide poisoning (0,010), and by washed spray equipment with levels of pesticides poisoning (0,026).